Critical Care Physiology - Robert H. Bartlett (MPublishing, 2010)
From the preface: "Critical Care Physiology, as the companion piece to The Michigan Critical Care Handbook...provides the explanations, references, methods, and other supportive information to flesh out the essentials presented in the handbook. Critical Care Physiology is limited to discussion of four organ systems (cardiovascular, respiratory, renal, and neurologic) and four topics in integrative physiology (oxygen kinetics, fluids and electrolytes, host defenses, and metabolism and nutrition)."